ON THE UNIVERSAL HUMAN CONTENT AND THE NATIONAL FORM OF CULTURE - Брагина, Дария (SWorldJournal, 2021)
In the context of the interaction of the processes of globalization and regionalization, the methodology for studying the problems of the functioning of national cultures becomes relevant. The purpose of this article is to draw attention to important aspe